Hsp104 facilitates the endoplasmic‐reticulum–associated degradation of disease‐associated and aggregation‐prone substrates. (20th May 2019) - Doonan, Lynley M.; Guerriero, Christopher J.; Preston, G. Michael; Buck, Teresa M.; Khazanov, Netaly; Fisher, Edward A.; Senderowitz, Hanoch; Brodsky, Jeffrey L.
Abstract: Misfolded proteins in the endoplasmic reticulum (ER) are selected for ER‐associated degradation (ERAD). More than 60 disease‐associated proteins are substrates for the ERAD pathway due to the presence of missense or nonsense mutations. In yeast, the Hsp104 molecular chaperone disaggregates detergent‐insoluble ERAD substrates, but the spectrum of disease‐associated ERAD substrates that may be aggregation prone is unknown. To determine if Hsp104 recognizes aggregation‐prone ERAD substrates associated with human diseases, we developed yeast expression systems for a hydrophobic lipid‐binding protein, apolipoprotein B (ApoB), along with a chimeric protein harboring a nucleotide‐binding domain from the cystic fibrosis transmembrane conductance regulator (CFTR) into which disease‐causing mutations were introduced. We discovered that Hsp104 facilitates the degradation of ER‐associated ApoB as well as a truncated CFTR chimera in which a premature stop codon corresponds to a disease‐causing mutation. Chimeras containing a wild‐type version of the CFTR domain or a different mutation were stable and thus Hsp104 independent. We also discovered that the detergent solubility of the unstable chimera was lower than the stable chimeras, and Hsp104 helped retrotranslocate the unstable chimera from the ER, consistent with disaggregase activity. To determine why the truncated chimera was unstable, we next performed molecular dynamics simulations and noted significant unraveling of the CFTR nucleotide‐binding domain. Because human cells lack Hsp104, these data indicate that an alternate disaggregase or mechanism facilitates the removal of aggregation‐prone, disease‐causing ERAD substrates in their native environments.